Analisis Instrumen Soal Tes Sumatif 1 Mata Pelajaran PKN Sekolah Dasar Negeri Se-Kabupaten Musi Rawas Utara - Masrohan; Puspa Djuwita; Osa Juarsa (UNIB Press, 2023)
The purpose of this study was to determine how the quality of multiple choice items in terms of material, construction, and language aspects. The formulation of the problem in this study is how the quality of multiple choice items in elementary schools in Muratara district for the 2019/2020 academic year. This research uses descriptive quantitative research. The sample used was 156. Sources of data in the study were question compilers, grade VI teachers at the Musi Rawas Utara Regency, and documentation. Analysis of multiple choice items used qualitative and quantitative analysis. Qualitative analysis used content validity analysis techniques according to Gregory, and matching cognitive domains. Quantitative analysis uses the help of the Anates V4 program. The results of this study indicate that multiple choice questions analyzed in terms of material, construction, and language aspects have very high categorical content validity. Based on this research, the preparation of questions should be done through the item analysis stage, especially rational logical analysis, which includes the validity of the content and the level of difficulty, so that the questions compiled can be of quality.